Marching Band and Character Education in Islamic Boarding Schools - Rifaldi, Muhammad Ichsan; Syeilendra, Syeilendra (Indonesian Research Journal in Education |IRJE|, 2023)
Islamic boarding schools are educational institutions that provide an understanding of religion and commit to developing a strong character which is based on the Islamic values. This research aims to investigate information and provide an understanding of the role of marching bands in forming the students’ character in Islamic boarding schools. The research method used is qualitative, with data collection techniques through interviews, observation, and documents. The research participants consisted of marching band administrators, coaches, and students who were members of the marching band unit. The research results show that marching band activities effectively contributed to the development of student discipline, cooperation, creativity, and independence. This combination of training methods had created a holistic environment that supports the students' character development in Islamic boarding schools. Thus, marching band activities not only provide musical experience but also become a beneficial tool in forming strong character and integrity in students.